2005
DOI: 10.1111/j.1537-2995.2006.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled‐rate versus uncontrolled‐rate freezing as predictors for platelet cryopreservation efficacy

Abstract: The use of strictly equalized (1 degrees C/min) controlled-rate freezing, combined with an intensified cooling rate (2 degrees C/min) during the liquid-to-solid-phase transition period, allows advanced quantitative and qualitative PLT recovery, even though the minor intergroup differences for some variables were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
(25 reference statements)
4
18
1
Order By: Relevance
“…P‐selectin is stored in granules of platelets and translocated to the platelet surface upon cellular activation. As shown in this and previous studies, P‐selectin expression was markedly up regulated following cryopreservation . Similar to the response to PS blockage, when P‐selectin on CPPs was blocked by anti–P‐selectin, the phagocytic activity and release of inflammatory cytokines in THP‐1 cells coincubated with CPPs were also partially inhibited, although the inhibitory effects were slighter compared with PS (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…P‐selectin is stored in granules of platelets and translocated to the platelet surface upon cellular activation. As shown in this and previous studies, P‐selectin expression was markedly up regulated following cryopreservation . Similar to the response to PS blockage, when P‐selectin on CPPs was blocked by anti–P‐selectin, the phagocytic activity and release of inflammatory cytokines in THP‐1 cells coincubated with CPPs were also partially inhibited, although the inhibitory effects were slighter compared with PS (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…14 Studies of 6% DMSO cryopreserved human platelets reported in vitro recoveries ranging from 50 to 80%. [15][16][17] Similar in vitro recoveries of 70-80% have been reported in studies of canine platelets cryopreserved in 6% DMSO. 4,9 In this study, 6% DMSO platelets had a mean in vitro recovery of 72.8%, significantly lower than that of Thrombosol platelets (95.2%, P 5 .02).…”
Section: Discussionsupporting
confidence: 73%
“…7,20,21 In studies of cryopreserved human platelets, baseline (or unstimulated) P-selectin expression was increased (35%) compared with fresh platelets (9%), suggesting premature platelet activation during the freezethaw-wash process. 17 Cryopreserved human platelets showed reduced P-selectin expression after ADP stimulation, reflecting their decreased ability for normal activation.…”
Section: Discussionmentioning
confidence: 99%
“…Many laboratories have reported good results using a controlled‐rate freezing approach (Borderie et al ., ; Balint et al ., ); however, a ‘quick freeze’ (often, but not always correctly, equated with ‘vitrification’) has been demonstrated to be at least as effective (Cetinkaya and Arat, ; Tan et al ., ) or superior in terms of cell quality (Kuleshova et al ., ; Berz et al ., ). Cells frozen using P7 showed no vitrified glass state by visual inspection.…”
Section: Discussionmentioning
confidence: 98%